Metaphor as a Means of Expressing the Cultural Characteristics of the Text (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is devoted to the study of the importance of metaphor as a means of expressing the cultural characteristics of the text. Metaphors not only enrich the content of the text, but also convey to the reader information about national culture, values and worldview. The article analyzes various texts and identifies the linguistic and cultural and semantic features of metaphors. Metaphors act as a bridge in understanding cultural differences and developing intercultural communication. The results of the research show that metaphors are an important tool that reveals the integral connection between language and culture.